(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
CalorEase is a web application that tracks calories aimed at making it easy for individuals to monitor their daily nutrition consumption in a very efficient and convenient manner. CalorEase supports users in finding food products, entering consumed quantity, and having calculated results in terms of calories, proteins, carbohydrates, and fats. Real-time monitoring, user identification, and historical logs are among the features incorporated in CalorEase to provide a comprehensive and tailored nutrition management system. Developed on React.js, Node.js, and MongoDB, the application offers a seamless user interface as well as secure data management. Differing from most current platforms, which either appear cluttered or are paywalled, CalorEase is free of cost and is aimed at simplicity and ease of use. The objective of this project is to create a lean but effective utility for those seeking to enhance their food habits. This article describes the system design, implementation, and evaluation and compares it to other similar applications in the industry.